Enhancing Waiter Teamwork: Supervisory Strategies at Bhira Restaurant, Quest San Hotel Denpasar, Bali - Dewangga, I Komang Krisna; Sumerta, Ketut Eli (Bali Journal of Hospitality, Tourism and Culture Research, 2024)
This study investigates the efforts of supervisors to enhance teamwork among waitstaff at Bhira Restaurant, Quest San Hotel Denpasar, Bali. The research aims to identify the strategies employed by supervisors and the challenges they face in fostering effective teamwork. A qualitative descriptive approach was adopted, utilizing interviews, observations, and documentation as data collection methods. The data were analysed and categorized based on the research objectives. The findings reveal that supervisors employ several strategies to improve teamwork, including conducting training sessions, clarifying shared goals, boosting employee motivation, fostering a cooperative work environment, and providing regular briefings. However, these efforts are met with challenges such as employees' fear of conflict, lack of team commitment, avoidance of accountability, and indifference toward team outcomes. This study highlights the critical role of supervisory efforts in overcoming these obstacles to create a cohesive and productive team environment.